Penguatan Jiwa Kewirausahaan Mahasiswa melalui Seminar Interaktif Daring ‘Bikin Usaha Gak Harus Nunggu Lulus!’ di Kota Banjarmasin - Lalu Agustino; Muhamamad Ridhoni; Muhammad Nawawi (Pusat Riset dan Inovasi Nasional, 2025)
This community service activity aimed to foster the entrepreneurial spirit among university students through an interactive online seminar entitled “Starting a Business Doesn’t Have to Wait Until Graduation!” The seminar was designed to deliver education, motivation, and practical inspiration to encourage students to start entrepreneurial initiatives early. The activity was conducted via Zoom, with 100 registered participants and 85 full attendees. An educational-participatory approach was implemented by involving young entrepreneurs who had successfully started businesses during their university years. The evaluation was conducted using a Google Form. The results showed that 97% of participants found the seminar highly beneficial, 94% reported feeling more motivated to pursue entrepreneurship, and 90% stated that the online format remained interactive and effective. These findings suggest that interactive seminars based on real entrepreneurial experiences can serve as an effective nonformal strategy to enhance students’ entrepreneurial motivation. Moreover, this program supports the implementation of the Tri Dharma of Higher Education, particularly in community service activities that directly impact students. Future programs may be expanded through continuous mentoring, quantitative evaluations using pre- and post-test designs, and integration into higher education entrepreneurship curricula.